Carbon Revenues From International Shipping : Enabling an Effective and Equitable Energy Transition - Summary for Policymakers - Dominioni, Goran; Englert, Dominik; Salgmann, Rico; Brown, Jennifer (Washington, DC: World Bank, 2022)
The International Maritime Organization (IMO) is currently considering developing market-based measures to meet the objectives of its Initial Strategy on the Reduction of Greenhouse Gas (GHG) Emissions from Ships (Initial IMO GHG Strategy). While market-based measures are to reduce GHG emissions from international shipping as a matter of priority, some types of market-based measures, e.g. carbon levies or a cap-and-trade scheme without free distribution of emissions allowances, can raise significant revenues—thereby enabling an additional set of actions. Strategically using these revenues also appears more favorable than applying exemptions to address important equity considerations. Hence, the study investigates the unique potential of revenue-raising market-based measures to enable an effective and equitable energy transition and explores three questions: What could carbon revenues from international shipping be used for, who could be the recipients of such revenues, and how can adequate management of carbon revenues from international shipping be imagined? The study considers seven main revenue use options, of which some revenue uses appear more aligned with guiding principles of the Initial IMO GHG Strategy and other key desirable features (e.g., ability to deliver greater climate and development outcomes) than others. The analysis also suggests that splitting carbon revenues between the shipping sector and the use outside the sector could be a viable way forward. As primary recipients of carbon revenues, governments appear to be most suitable given the often blurred links between companies and countries in international shipping. However, to maximize climate and development outcomes, a share of carbon revenues may also be channeled to the private sector, including the shipping industry. The report stresses that expertise and experience from existing climate finance funds and international development organizations offering trustee services could be leveraged to inform and operationalize the management of carbon revenues from international shipping and to minimize transaction costs.